Phytoremediation of polycyclic aromatic hydrocarbons (PAHs) in mangrove sediments using Rhizophora mangle. (November 2020) - Verâne, Jéssica; dos Santos, Naiara C.P.; da Silva, Verônica L.; de Almeida, Marcos; de Oliveira, Olívia M.C.; Moreira, Ícaro T.A.
Abstract: A phytoremediation experiment was carried out in mesocosms to investigate the performance of Rhizophora mangle in the remediation of polycyclic aromatic hydrocarbons (PAHs) in mangrove sediment contaminated with crude oil. The water pH of the experiments (phytoremediation and natural attenuation) ranged from 4.9 to 8.4 at 0 and 90 days, respectively. The oxy-reduction potential (Eh) ranged from oxidising (108.0 mV, time 0) to reducing (approximately −110.0 mV, time 90) environments. Dissolved oxygen (DO) ranged from 5.7 mg L −1 (time 0) to 4.5 mg L −1 and 3.6 mg L −1 (time 90) in phytoremediation and natural attenuation, respectively. The sediments had silty texture and an average concentration of 5% organic matter (OM). Phytoremediation (60.76%) showed better efficiency in the remediation of the 16 PAHs compared to natural attenuation (49.57%). Principal component analyses showed a correlation between the concentrations of PAHs with pH, Eh, OM and DO in both experiments. Highlights: A phytoremediation system was developed to remove hydrocarbons in mangrove sediments. Rhizophora mangle had the phytoremediation potential for PAHs contaminated coastal sediments. R . mangle has not been affected by the toxic effects of PAHs compounds.